Influence of mineral fertilizers on productivity and grain quality in spring wheat Svecha - V. D. Abashev; F. A. Popov; E. N. Noskova; S. N. Zhuk (Аграрная наука Евро-Северо-Востока, 2017)
Results of researches in long-time stationary experiment on sod-podzolic middle clay soil formed on eluvia of Perm clays are presented in the article. Spring wheat Svecha was cultivated on a layer of clover of first year of use. Scheme of the experiment includes 54 variants. A range of fertilizers doses varied from 30 up to 150 kg of acting matter of nitrogen, phosphorus, and potassium. When doses of fertilizers increased productivity of spring wheat increased too; however, addition of yield decreased at each subsequent dose. Grain productivity of spring wheat Svecha was defined basically by application of nitric and phosphoric fertilizers and to a lesser degree - by potash. The greatest productivity is received at entering of full mineral fertilizer dose Ж0Р60К60 which has provided productivity of 3.27 t/ha that is 1.7 times high than without fertilizers. At this rate wheat production is most profitable at self-recoupment 3509 rubles per ton of grain. The greatest recoupment of 1 kg of fertilizers' acting matter by the basic production is received in variants with low doses of nitric and phosphoric fertilizers: N60 - 13.7 kg, Р60 - 11.7 kg, Ш0Р60 -10.8 kg of grain; the least one - of potash fertilizers: К60 - 3.0, К120 - 2.7 kg. Each increase in fertilizers doses led to decrease in a recoupment of grain of spring wheat; in a variant with the maximum dose Ш50Р150К150 - up to 2.9 kg. The size of a recoupment of fertilizers with grain is defined also by conditions of humidifying of the growing season. The least recoupment is noted in droughty 2016. Test weight of grain of spring wheat depended mainly on weather conditions of growing season and harvesting period. Input of mineral fertilizers does not influence on test weight. Bread from spring wheat flour has sufficient quality which does not governed by dozes of fertilizers.